Assessment of Physio-Chemical Properties of Bahir Dar Textile Sludge and Its Impact on The Growth of Lettuce (Lactuca Sativa) and Soil Nutrient Improvement - Degu, Adise; Shiferaw, Tesfaye; Feyisa, Tesfaye (Journal of Tropical Crop Science, 2025)
Textile produces large volumes of sludge due to industrial activity, and its disposal is a serious environmental concern because it includes toxic contaminants, including heavy metals. Due to its vast volume and mass, sludge management is seen as an additional burden to the industry. This study aims to characterize solid sludge from the textile industry. The sludge’s pH, organic matter (OM), nutrient elements (N, P, K), and metal content were determined using appropriate analytical techniques. Treatment consisted of 4×3 factorial combinations of nitrogen and phosphorus, i.e., full recommended (100 kg N and 50 kg P), half recommended (50 kg N and 25 kg P), control, and dried sludge at 0, 5, 10, and 20 tons per ha. The textile industrial sludge’s Cu, Cr, Fe, Cd, Pb, and Zn concentrations are 511.568, 251.166, 7991.667, 67.333, and 463.00, respectively. The Cu, Cr, Fe, and Zn concentration levels exceeded the recommended upper limit for agricultural soil. Nonetheless, cadmium and lead are below WHO standards. Soil pH, % total nitrogen, % total organic content, and % organic matter increased after sludge application. Applying textile sludge to soil considerably raised the soil Cr, Fe, and Cu contents compared with the control, and lettuce growth increased from 75 g to 143.5 g per pot after applying 20 tons of sludge per ha. Therefore, textile sludge could be an alternative to organic fertilizer or soil conditioner if metals, especially Fe and Cr, are reduced by proper treatment strategies.